2015
DOI: 10.1136/bcr-2014-208768
|View full text |Cite
|
Sign up to set email alerts
|

Wearable technology: using Google Glass as a teaching tool

Abstract: Wearable technology holds great promise in revolutionising healthcare delivery. The benefits can also be seen in medical education and delivering healthcare in remote places. We report the use of Google Glass technology as a teaching tool in broadcasting a procedure onto a mobile phone as a viewer, replacing expensive and often cumbersome existing equipment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 6 publications
0
28
0
Order By: Relevance
“…Fifteen of the 34 articles (44%) featuring the use of Google Glass were primary research articles;2 5 8 10 11 15 16 19 21 26 28 31 32 35 36 of these, 12 described either exploratory studies or ‘proof-of-concept’ case studies in clinical settings. In general, all of these studies concluded that Google Glass has the potential to enhance various aspects of surgery, but the majority highlighted functional limitations (eg, limited battery life, insufficient resolution and rudimentary voice control), usability issues (eg, incompatibility with surgical loupes, mismatch between the user's natural line of sight and the position of the display) and privacy concerns as significant barriers to practical clinical implementation.…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen of the 34 articles (44%) featuring the use of Google Glass were primary research articles;2 5 8 10 11 15 16 19 21 26 28 31 32 35 36 of these, 12 described either exploratory studies or ‘proof-of-concept’ case studies in clinical settings. In general, all of these studies concluded that Google Glass has the potential to enhance various aspects of surgery, but the majority highlighted functional limitations (eg, limited battery life, insufficient resolution and rudimentary voice control), usability issues (eg, incompatibility with surgical loupes, mismatch between the user's natural line of sight and the position of the display) and privacy concerns as significant barriers to practical clinical implementation.…”
Section: Resultsmentioning
confidence: 99%
“…Other applications include Glass being used for Disaster Telemedicine triage; however, no increase in triage accuracy was found [ 28 ]. Google Glass was used to play recorded video for mentoring purposes [ 29 ], and has also been used to address communication and education challenges in a telemedicine context [ 30 ]. Research has also explored pre-hospital care, in which Glass acted like a console for transferring patient data [ 31 ]; however, Glass could not show any advantage compared to mobile devices in this study.…”
Section: Background and Related Workmentioning
confidence: 99%
“…The development of compact telementoring platforms, such as Google Glass™, provides students with tailored feedback and reduces procedural complication risk of teaching students, creating an ethical impetus for these high-fidelity technologies [9]. Telementoring technologies establish an active connection to the procedure, wherein a distant surgeon can guide a trainee as they learn a new procedure or encounter an unexpected emergency [6,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Telementoring may also benefit practicing physicians by providing a dynamic and effective method of teaching, even when trainers or trainees are at remote locations [9]. Medical education may be more effectively distributed to trainees while allowing attending surgeons to direct more of their time toward their practice [3,12,15].…”
Section: Introductionmentioning
confidence: 99%